PENGEMBANGAN MEDIA CHART BERGAMBAR DALAM PEMBELAJARAN IPS - Waluyo Waluyo; Sudjarwo Sudjarwo; R Gunawan Sudarmanto (Faculty of Teacher Training and Education, University of Lampung, 2013)
This research aimed to produce of media pictured chart of Social Studies and to know the extent of effectiveness of media pictured chart in Social Studies learning. The research method used was Research and Development (RD). The design of media development used instructional design steps of Dick and Carey. The result of the development research concluded that, (1) media expert, content expert, teaching-learning expert and students toward the product developed had good criteria, relevant, appropriate, attractive, clear, interesting enough and help the learning process of Social Studies and was stated fit for use; (2) the result of product trial of media pictured chart developed got the conclusion that the average of experimental class learning result used media chart was higher than control class which used conventional media. The result analysis of try out got coefficient score of t count was higher than t table so that media pictured chart learning was stated effective.Penelitian ini bertujuan menghasilkan produk berupa media chart bergambar IPS dan untuk mengetahui sejauh mana efektivitas media chart bergambar dalam pembelajaran IPS. Metode penelitian yang digunakan adalah Research and Development (RD). Desain pengembangan media menggunakan langkah-langkah desain instruksional Dick and Carey. Hasil penelitian pengembangan ini menyimpukan bahwa, (1) penilaian ahli media, ahli materi, ahli pembelajaran dan peserta didik terhadap produk yang dikembangkan memiliki kriteria baik, relevan, sesuai, menarik, jelas, cukup menarik dan membantu proses pemebalajran IPS dan dinyatakan layak digunakan; (2) hasil uji coba produk media chart bergambar yang dikembangkan diperoleh kesimpulan bahwa rata-rata hasil belajar kelas eksperimen yang menggunakan media chart bergambar lebih tinggi dari pada kelas kontrol yang menggunakan media konvensional. Hasil analisis uji coba diperoleh nilai koefisien t hitung lebih besar dari t tabel sehingga pembelajaran dengan media chart dinyatakan efektif.Kata kunci : media chart bergambar, pembelajaran ips, pengembangan